2017
DOI: 10.1016/j.cell.2016.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Chimerism with Mammalian Pluripotent Stem Cells

Abstract: SUMMARY Interspecies blastocyst complementation enables organ-specific enrichment of xenogenic pluripotent stem cell (PSC) derivatives. Here, we establish a versatile blastocyst complementation platform based on CRISPR-Cas9-mediated zygote genome editing and show enrichment of rat PSC-derivatives in several tissues of gene-edited organogenesis-disabled mice. Besides gaining insights into species evolution, embryogenesis, and human disease, interspecies blastocyst complementation might allow human organ generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
405
5
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 437 publications
(435 citation statements)
references
References 58 publications
(70 reference statements)
9
405
5
16
Order By: Relevance
“…So, although mouse is the most accessible animal in terms of obtaining embryos, when analyzing human cells other hosts more closely related to humans should be considered. In support of this, Wu et al (2017) reported successful chimera formation using human primed PSCs transplanted into porcine embryos -albeit at a very low rate and degree of chimerism -whereas chimeras were not obtained when rodent naïve PSCs were transplanted. These results highlight the importance of genetic/evolutionary distance when generating interspecies chimeras.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…So, although mouse is the most accessible animal in terms of obtaining embryos, when analyzing human cells other hosts more closely related to humans should be considered. In support of this, Wu et al (2017) reported successful chimera formation using human primed PSCs transplanted into porcine embryos -albeit at a very low rate and degree of chimerism -whereas chimeras were not obtained when rodent naïve PSCs were transplanted. These results highlight the importance of genetic/evolutionary distance when generating interspecies chimeras.…”
Section: Introductionmentioning
confidence: 72%
“…However, in both cases, the frequency of chimeric embryos among all injected embryos was remarkably low, and the degree of chimerism -the contribution of the PSC-derived cells to the chimera -was far below the level found in mouse-rat interspecies chimera (Kobayashi et al, 2010;Isotani et al, 2011;Yamaguchi et al, 2017;Wu et al, 2017). Other groups have reported that engrafted human naïve-like PSCs disappear after implantation, or in some cases survive but contribute only to the extraembryonic region (Takashima et al, 2014;Masaki et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…One way in which this can be achieved is through interspecies blastocyst complementation. In this technique, a non-human animal blastocyst is obtained from a mutant strain in which 'a gene critical for the development of a particular lineage is disabled' (Wu et al, 2016(Wu et al, , 2017. Afterwards, this blastocyst is complemented with human stem cells, which will compensate for the existing niche.…”
Section: Introductionmentioning
confidence: 99%